Use of suspensions of phytosterol microparticles to improve the solubility of methane in water☆ - Gallard Jeanne; Wantz Eliot; Hébrard Gilles; Bouchoux Antoine; Mouloungui Zéphirin; Valentin Romain (Oilseeds and fats, crops and lipids)
Methane, an abundantly produced greenhouse gas, is a major driver of global climate change. The development of sustainable processes for methane capture is limited by the poor solubility of this organic compound in water, but this solubility can be increased by adding other compounds to the aqueous solution. Here, we studied the solubility of methane in aqueous dispersions containing lipid microparticles of phytosterols—a group of sterol compounds from plants—at room temperature and atmospheric pressure. The solubility of the phytosterols in water was improved chemically, by functionalization with glycerol carbonate in solvent-free conditions, and physically, by antisolvent precipitation to form particles in water. We evaluated the influence of phytosterol microparticles on methane solubility in water by monitoring the apparent partition coefficient between the gas and liquid phases defined by Henry’s law. Phytosterol functionalization generated amphiphilic phytosterols with glycerol branches, which were characterized by FTIR and MALDI-TOF. These amphiphilic phytosterols formed particles of 2 and 12 μm in diameter on antisolvent precipitation. Systems containing phytosterol microparticles had a partition coefficient half that of the corresponding control. The gas-liquid equilibrium was, therefore, shifted to the liquid state, demonstrating that the solubility of methane in water was improved by phytosterol microparticles.